OBSTACLES IN MANAGING GIANT PROLACTINOMA: A SUDDEN RESURGENCE WITH NEW ONSET SEIZURE IN GIANT PROLACTINOMA - Daud, Siti Zakiah Ahmad; Abas, Syarifah Syahirah Syed; Karim, Nor Afidah; Sin, Yong Lit; Adam, Noor Lita (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Sarcoidosis is a multisystem granulomatous inflammatory disorder with common involvement of the lungs, lymph nodes and heart. Neurosarcoidosis, especially hypothalamicpituitary involvement, is a rare phenomenon (<10% of sarcoidosis patients). Recognizing this holds significance in guiding investigations and early commencement of treatment. CASE A 32-year-old nulliparous female with no prior medical illness, presented to the ophthalmology clinic with 6 months history of painless red eye, without cough or constitutional symptoms. She was managed as a case of left eye anterior uveitis. Further assessment to exclude tuberculosis revealed perihilar lobulated opacities on CXR, negative serial sputum AFB and positive tuberculin skin test (Mantoux) of 16mm. CT of the thorax showed multiple lung nodules with lymphadenopathies involving cervical, mediastinal, hilar and axillary regions. Bronchoscopy was negative for TB PCR and MTB culture had no growth. She was treated for latent PTB for 3 months. Further history revealed secondary amenorrhea and polyuria with polydipsia. Pituitary workup confirmed hypogonadotrophic hypogonadism [serum FSH: 2.9 IU/L, LH: 1.13 IU/L, estradiol: 52.8 pmol/L]. After an overnight water fasting, serum osmolality increased to 301 mOsm/kg, with hypernatremia (serum Na: 151 mmol/L) and markedly diluted urine (urine osmolality: 45 mOsm/kg). These were all suggestive of central diabetes insipidus. Other pituitary hormones were normal [serum cortisol: 573.5 nmol/L, TSH: 1.916 m IU/L and prolactin: 331.1 mU/L]. Pituitary MRI revealed an absence of a posterior pituitary bright spot, without a pituitary lesion. Since TB has been ruled out, multi-systemic sarcoidosis was considered. Serum angiotensin-converting enzyme was elevated at 72.80 U/L (NR 8-52). A respiratory consult concluded a stage 2 pulmonary sarcoidosis. She was started on oral desmopressin 60 mcg BID and hormone replacement therapy. Oral prednisolone at a dose of 0.5 mg/kg/day was initiated for sarcoidosis treatment. CONCLUSION Neurosarcoidosis is often diagnosed late due to a low index of suspicion. It should be included in the differential diagnosis when patient presented with hypothalamicpituitary disorder as it is associated with higher morbidity. Corticosteroids and simultaneous hormonal therapy remain the mainstay of treatment.